Re-Visioning Gender Relationships in the Organization - Marshall, Judi (Feminist theology, 1994)
Callaway (1981) calls the process of re-appraisal of women's characteristics, social roles and culture, independent of male value systems...'re-vision', and identifies three ways it can describe women's current activities: 'Revision' in the standard sense of correcting or completing the record; then 're-vision' as looking again, a deliberate act to see through the stereotypes of our society as these are taken for granted in daily life and deeply embedded in academic tradition; and finally, 're-vision' in its extended sense as the imaginative power of sighting possibilities and thus helping to bring about what is not (or not yet) visible, a new ordering of human relationships (Marshall 1992: 76).